Humanisme Pendidikan Islam (Telaah Buku Pendidikan Inklusi di Pondok Pesantren Karya Nurul Azizah Dkk) - Azizah, Marifatul; Munawaroh, Anirotul (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Inclusive education within Islamic boarding schools (pesantren) often faces a gap between theological idealism and the reality of managerial governance. This study aims to critically review the book Pendidikan Inklusi di Pondok Pesantren by Nurul Azizah et al. through the lens of the Islamic Educational Humanism Theory. Utilizing a library research method with a descriptive-critical approach, this article dissects the book's content based on three main pillars: karamah insaniyyah (human dignity), al-’adalah wa al-musawah (justice and equality), and al-rahmah wa al-tasamuh (compassion and tolerance). The novelty of this research lies in its position as a critical partner that does not merely summarize the authors' empirical data passively, but rather tests the validity of these field practices while identifying managerial gaps left unresolved in the primary text. The results of the review indicate that pesantren possess highly robust cultural and religious capital, wherein traditional teaching methods like sorogan effectively function as a form of fair curriculum modification for students with special needs. However, this study reveals substantial limitations within the book regarding the formulation of accessible physical infrastructure management and standardized academic assessment instruments. The implication of this study offers a synthesized model of inclusive education management that is not only structurally applicable but also deeply rooted in the theological traditions of Nusantara Islam